Effects of Technology-Based Education on Health Literacy Among Elderly Monks with Hypertension - Seedacam, Chatree; Rhiantong, Jittawadee; Panuthai, Sirirat (Nursing Journal CMU, 2024)
Hypertension has been found to have a high incidence among elderly monks. Technology-based education through a health literacy program may help elderly monks with hypertension to improve their health literacy. This experimental research aimed to study the effects of technology-based education on health literacy among this group. The sample group consisted of elderly monks diagnosed with hypertension who received care at Health Promoting Hospitals in Mueang Nakhon Sawan District, Nakhon Sawan Province. A total of 54 participants selected by simple random sampling were divided into a control group and an experimental group of 27 each. The experimental group received four sessions of group teaching and one session of individual teaching throughout a span of three weeks, while the control group received usual care. Data collection instruments included 1) an interview form on personal and illness data and 2) an interview form on health literacy for elderly monks with hypertension. The program on technology-based education for health literacy was checked for content validity by five experts. Regarding the measurement tool, an interview form on health literacy for elderly monks with hypertension, the researcher tested its internal consistency and obtained a Cronbach's correlation coefficient of .85. The data were analyzed using descriptive statistics, independent t-test, and dependent t-test. The results showed that after receiving the technology-based education program, the experimental group had higher mean scores for health literacy (M = 45.41, SD = 2.64) than those of the control group who received usual care (M = 19.93, SD = 3.03) with a statistically significant difference (t = 33.01, p < .001) and a higher mean score than before receiving the program (M = 20.74, SD = 3.21) with a statistically significant difference (t = -46.68, p < .001). In conclusion, the technology-based education program effectively improves health literacy. Healthcare professionals can apply the technology-based education program to promote health literacy promotion among elderly monks with hypertension.